Study temperature effect on metallurgical properties of semi-solid state joining of aluminum SSM 356 - Khrueaphue, Thongchai; Muangjunburee, Prapas (Asia-Pacific Journal of Science and Technology, 2017)
The purpose of this research was to study the welding condition of semi-solid metal (SSM) 356 which casted by Gas Induced Semi-Solid technology or GISS technique; to compare the transformation of metallurgical properties of welding joint; and to find suitability of parameter in welding, welding parameter of straight cylindrical using rotating speed rate of pin at 1,110 and 1,320 rpm, welding speed at 120 and 160 mm/min, tilt angle pin at 2 degree, heat with carburizing fame at 575-590 oC and 590-610 oC and using Data Logger as the temperature measurement. From the experiment, it was found that the temperature while welding of the two parameters was in the control period needed which depending on heating factor from flame, speed rotation of pin and welding speeds. From examining the surface appearance of welding, it was not the straight line and obviously waving appearance. However, at 1,100 rpm – 120 mm/min and the temperature while welding at 590-610 oC, the surface appearance of welding was the most fine-looking and complete – straight line and no waving appearance. From examining the macrostructure, it was found that welding joint was not union in addition to the occurrence of a little pneumatic space at the upper part of the welding joint. Nevertheless, the best macrostructure was at 1,110 rpm – 120 mm/min, welding temperature at 590-610 oC which the welding joint was in well connecting. From examining the microstructure, it found the little pneumatic space throughout the welding joint area and eutectic phase basin was occurred in the welding joint area. It was found that the best microstructure was at 1,110 rpm-120 mm/min, welding temperature at 590-610 oC which was no pneumatic spaces and the appearances of grain was a round lump with similar size and well spreading in the area of welding joints.